Chapter 4 Innovation in Early Music Festivals Domains, Strategies and Outcomes - Castro-Martínez, Elena (Taylor & Francis, 2022)
book fairs, creative industries, cultural effects, digital age, food events, management, music festivals, organization, publishing, strategy, UNESCO heritage, Venice Biennale